Unveiling the multifunctionality of iron oxide nanoparticle: A synergistic experimental and computational investigation - Shiva Sharma; Sudheesh K. Shukla; Krishna K. Govender; Penny P. Govender (Chemical Physics Impact)
Iron oxide nanoparticles (IONPs) are known for their multifunctionality in diverse biomedical, environmental, and catalytic areas, controlled by their size, shape, phase, and surface properties. Thermal decomposition, sol-gel, co-precipitation, hydrothermal techniques, and green synthesis are the different ways to synthesize IONPs. These techniques offer control over size, morphology, and phase, which influences the intrinsic properties of the IONPs. Surface functionalization with ligands or polymers played another important role in improving the physicochemical properties, environmental application, and biological interactions of IONPs. Experimental and computational approaches can be used to evaluate these characteristics and perform controlled reactions. In this review, we attempt to compile the recent studies on computational methods used to evaluate the intrinsic properties concerning shape, size, structure, and phases, optimized synthesis, functionality of IONPs for drug delivery, biomedical imaging, dye degradation, and water remediation. Integrating advanced computational tools with experimental methods promises new opportunities for designing multifunctional IONPs for specific industrial, medical, and environmental applications. This study highlights how synthesis methods like thermal decomposition, sol-gel, and hydrothermal techniques enable control over IONP size, morphology, and phase. Surface functionalization enhances stability, biocompatibility, and functionality. Computational tools like DFT provide insights into material properties, enabling optimized design for drug delivery, imaging, dye degradation, and water remediation applications.